The effect of superdisintegrants on the dissolution of atenolol fast dissolving tablets - P.Vinay Kumar; G. Sushma; Ganesh Kumar Gudas (International Journal of Pharmacy and Analytical Research, 2022)
In the present study an attempt has been made to prepare fast dissolving tablets of atenolol, by using different superdisintegrants with enhanced disintegration & dissolution rate. Atenolol is a potent Antihypertensive agent. It competes with sympathomimetic neuro transmitters such as catacholamines such as catecholamines for binding at beta (1) - adrenergic receptors in the heart and vascular smooth muscle, inhibiting sympathetic stimulation. Fast dissolving tablets of atenolol were prepared b y using different natural superdisintegrants like fenugreek seed mucilage, Modified Gum karaya and Locust bean gum by direct compression. The precompression blend was tested for angle of repose, bulk density, tapped density, compressibility index and Hausner’s ratio. The tablets were evaluated for weight variation, hardness, friability, disintegration time (1 min), dissolution rate, content uniformity, and were found to be within standard limit. It was concluded that the fast dissolving tablets with proper hardness, rapidly disintegrating with enhanced dissolution can be made using selected superdisintegrants. Among the different formulations of atenolol prepared and studied, the formulation F12 containing Locust bean gum was found to be the fast dissolving formulation.